126k views
5 votes
B jada writes this equation for the sum of the ages (x)+(x+3) +3(x+3)-1=87 explain the meaning of the variable and each term of the equation.

1 Answer

5 votes

Answer:

Please check the explanation.

Explanation:

Given the equation


(x)+(x+3) +3(x+3)-1=87

simplifying the equation


x+x+3+3x+9-1=87

adding similar elements


(x+x+3x)+(3+9-1-87)=0


5x-76=0

Thus, the equation is a linear equation in one variable 'x'.

A term is a single mathematical expression, so the simplified expression has two terms which are:

  • 5x
  • -76

The term 5x has the variable 'x' of power 1.

The term -76 does not involve any variable, Hence, -76 is a constant term.

User Alex Punnen
by
5.1k points